Leading people on foot to the police headquarters - Badara, Adrian Daniel (Eximia, 2023)
Driving to the police headquarters is carried out when it is necessary for the detected person to be brought to the police headquarters for certain measures that must be taken to solve certain police procedures. Also, driving to the police headquarters is justified, as a decision to protect the person, when taking legal measures, on the spot, could create a danger for it or for public order. Since driving at the police headquarters affects individual freedom, the obligation of the police officer to report on the application of this measure is established. Police officers carry out driving at the police headquarters, by accompanying people, in order to take legal measures. The verification of the situation of these categories of persons and the taking of legal measures, as the case may be, is carried out in no more than 24 hours. If the policeman acts alone, he asks for the support of the citizens, whom he informs about what they have to do, so that this police measure can be successfully carried out. This procedure does not exclude or limit the obligation of the personnel involved in these activities to comply with and comply with the normative acts/provisions in force, as well as the provisions of the Organization and Operation Regulation and the Job Description.